Characterization of initial ankle-foot prosthesis prescription patterns in U.S. Service members following unilateral transtibial amputation - Monaghan, Patrick G.; Knight, Ashley D.; Brinkerhoff, Sarah A.; Harrison, Kenneth D.; Dearth, Christopher L.; Hendershot, Brad D.; Sefton, JoEllen M.; Zabala, Michael; Vazquez, Adan; Shannon, David; Crumbley, David; Roper, Jaimie A. (Frontiers in Rehabilitation Sciences, 2023)
The purpose of this study was to explore relationships between patient-specific characteristics and initial ankle-foot prosthesis prescription patterns among U.S. Service members with unilateral transtibial limb loss. A retrospective review of health records identified 174 individuals with unilateral transtibial limb loss who received care at Walter Reed National Military Medical Center between 2001 and 2019. We examined patient-specific factors such as demographics, participant duty status at injury and amputation, amputation etiology, and timing between injury, amputation, and initial prescription. The type of first prescribed ankle-foot prosthesis was categorized as energy-storage-and-return and articulating, energy-storage-and-return and non-articulating, or computer controlled. Sex, amputation etiology, time from injury to initial prescription, and time from amputation to initial prescription differed by type of initial ankle-foot prosthesis prescription. Service members with shorter intervals between injury-initial prescription and amputation-initial prescription, and those injured by combat blast, were more likely to receive a non-articulating device. Incorporating sex, time from injury-initial prescription, time from amputation-initial prescription, and amputation etiology as predictors of prosthesis type, we were able to correctly classify 72% of all first prostheses prescribed. Patient-specific characteristics such as sex, the time between injury-initial prescription, time from amputation-initial prescription and amputation etiology are essential characteristics that influence initial ankle-foot prosthesis prescription patterns in U.S. Service members.